Genetic Characterization of HIV Type 1 Tat Exon 1 from a Southern Indian Clinical Cohort: Identification of Unique Epidemiological Signature Residues - Neogi, Ujjwal (Mary Ann Liebert, Inc., 2012)
The trans-activator of transcription (Tat) of HIV-1 plays an important role in viral infection and pathogenesis. We examined the genetic characteristics of exon 1 of the tat gene derived from 102 seropositive subjects from southern India. Database-derived Indian (n=105) and global (n=413) HIV-1C sequences were also used for viral epidemiological signature pattern analysis in the Tat open reading frame (ORF). We identified HIV-1C as the most predominant genetic subtype (99%) and the presence of a novel A1C recombinant strain in one study participant. After examining all the available HIV-1C Indian sequences from primary clinical isolates and database-derived sequences, we found a high level of sequence conservation (92.6±12%) within Tat amino acid residues. Furthermore, signature pattern analysis identified five amino acid positions in Tat that contained signature residues unique for Indian HIV-1C consisting of 21A, 24N, 29K, 40K, and 60Q. Our data have direct relevance for subunit-based Tat HIV-1 vaccine development.